Friction Characteristic Switching Function and Ultra-Precision Positioning of Multilayer Electrostatic Actuator - Md Ghazaly, Mariam (2012)
The present paper describes the characteristic switching of a multilayer thin electrostatic actuator supported by only lubricating oil and its application in the control of an ultra-precision fine stage.